KEADAAN ELEMEN JALAN HUTAN DAN POTENSINYA DALAM MEMPERCEPAT EROSI TANAH - Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
A study on the forest road element conditions in relation to soil erosion potentials was carried out at two logging companies in Buntok area, Central Kalimantan in 1988. Road elements measured in the field are those related to the Universal Soil Loss Equation factors such as road openings, surfaces, slopes, ditches, culverts, cuts, fills, diversion ditches, and the incidence of vegetation.The results showed that forest road elements are in the condition of high potentials for accelerating soil erosion.Factors that caused this problem, as identified in the field, are: long and steep slopes, wide ground openings, and bare soil surfaces, in addition to the originally sensitive to erosion soil type, and hot and wet weather.Qualitatively, it is realized that soil erosion is quite serious. Therefore, further study is necessary in order to find the quantitative amount of soil erosion occured in the area.